Noviazgos largos-convivencias matrimoniales efímeras - Armentia Espigares, Laura ca. 21. Jh. (Estudios eclesiásticos, 2008)
Because of my job as part of the Court of Rota from the Spanish Apostolic Nunciature I have recently noticed a reality that arouses my interest because of its prevalence and because of its legal, canonical and pastoral consequences. Often marital coexistence lasts only a few months even though it has been surprisingly preceded by an extraordinary long engagement, of, at least, eight years. In order to evaluate this situation I have considered several real cases processed in our ecclesiastical court. After deeply analyzing them, several data and different considerations are done, special mention given to the probatory law in relation the subject. This article ends up with some personal considerations and thoughts related to these situations.